2010
DOI: 10.1007/s00125-010-1757-1
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytes promote albuminuria, but not renal dysfunction or histological damage in a mouse model of diabetic renal injury

Abstract: These results show that lymphocytes contribute to the development of diabetic albuminuria, which may partly arise from increasing glomerular macrophage activation and podocyte damage. In contrast, lymphocytes do not appear to promote tubular injury, increased matrix deposition or decline in renal function in a mouse model of type 1 diabetes. Our findings suggest that innate immunity rather than adaptive immune responses are the major inflammatory contributor to the progression of diabetic renal injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 31 publications
3
58
0
2
Order By: Relevance
“…Indeed, there were no significant changes in other infiltrating immune cell types identified between diabetic mouse groups in the present study. This is consistent with a previous report from our group [23] suggesting that macrophages are the major immune cells contributing to renal functional changes and tubulo-interstitial fibrosis in experimental diabetes. There Cortical HMGB-1 (ng/mg protein) was evidence of reconstitution of glomerular cells by bone marrow from both donor groups as has been previously shown in diabetes [24], but the relative contribution of these remains to be delineated in future studies.…”
Section: Discussionsupporting
confidence: 94%
“…Indeed, there were no significant changes in other infiltrating immune cell types identified between diabetic mouse groups in the present study. This is consistent with a previous report from our group [23] suggesting that macrophages are the major immune cells contributing to renal functional changes and tubulo-interstitial fibrosis in experimental diabetes. There Cortical HMGB-1 (ng/mg protein) was evidence of reconstitution of glomerular cells by bone marrow from both donor groups as has been previously shown in diabetes [24], but the relative contribution of these remains to be delineated in future studies.…”
Section: Discussionsupporting
confidence: 94%
“…8,[10][11][12]32 Animal model studies have demonstrated that glomerular levels of IgG increase with the duration of diabetes and correlate with albuminuria and renal inflammatory infiltrate. [33][34][35] Our study reveals glomerular immune deposits and high levels of total and oxidized LDL-specific antibodies in diabetic hypercholesterolemic mice, without differences between apoE and gapoE mice. Further analysis of IgM/IgG and Th1/Th2 ratios did not substantiate changes in lymphocyte responses.…”
Section: Discussionmentioning
confidence: 67%
“…Real-time PCR analysis was performed as previously described. 28 The Taqman probe and primer sequences are listed in Supplemental Table 3. Figure 7.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…26 Immunoperoxidase staining for leukocytes (CD68, CD3, Ly6g) was performed on 2% paraformaldehydelysine-periodate-fixed kidney cryostat sections and assessed using established protocols. 28 Immunoperoxidase staining for MR, a-smooth muscle actin, activated caspase-3, and Wilms' tumor-1 was performed on formalin-fixed sections (4 mm) and analyzed according to a previous report. 28 All scoring was performed on blinded slides.…”
Section: Histology and Immunostainingmentioning
confidence: 99%
See 1 more Smart Citation